AB0943 Significance of muscle volume & fatty degeneration of lumbar paraspinal muscle in spinal imbalance. (15th June 2017) - Park, Y-S; Lee, J; Park, J-S
Abstract : Background: Spinal sagittal imbalance which is closely associated with low back pain is considered as a factor in a variety of spinal disorders. Objectives: The present study was to determine the relationship between the sagittal imbalance and sarcopenia, especially cross sectional area (CSA) and fatty degeneration (FD) of muscle around the spine. Methods: Overall, 165 patients are included in this study, classified by three groups according to the distance from sagittal vertical axis to posterior end of upper end plate of sacrum. 38 patients were classified as group 1 (distance ≥9cm), 50 and 53 patients as group 2 (distance 5–9cm) and group 3 (distance <5cm), respectively. For measurement of CSA and FI of paraspinal muscles, five transverse T1W images of S1-S5 were obtained from PACS and measured with Adobe Photoshop 7.0®, by counting the number of pixels included in each selected muscle area. A variance analysis on average muscle surface area of those five images was done with SPSS 19.0 Windows version (SPSS Inc., Chicago, IL, USA). Results: The average age of total patients was 69.1, average BMI was 22.57 and bone density was -2.34 (T-score). No significant differences were detected on ages, BMI, and bone density. Each correction coefficient of multifidus, erector spinae and psoas muscle was 0.80, 0.75 and 0.81, respectively. CSA of paraspinal muscles has significant differences between group I and III, II and III. Psoas has significant differences between all groups. FI has significant differences between all groups in multifidus and between I and III, II and III in erector spinae. But, psoas has no significance between three groups. Conclusions: Authors were able to detect significant muscle atrophy in the group with severe imbalance. And degeneration of paravertebral muscle has significant increased with sagittal imbalance. Effort for preventing weakness of muscle around spine might cause influence to alignment of spine. References: Fortin M, Lazáry À, Varga PP, McCall I, Battié MC. Paraspinal muscle asymmetry and fat infiltration in patients with symptomatic disc herniation. Eur Spine J Off Publ Eur Spine Soc Eur Spinal Deform Soc Eur Sect Cerv Spine Res Soc 2016;25:1452–9. doi:10.1007/s00586–016–4503–7. Lee SH, Park SW, Kim YB, Nam TK, Lee YS. The fatty degeneration of lumbar paraspinal muscles on computed tomography scan according to age and disc level. Spine J Off J North Am Spine Soc 2016. doi:10.1016/j.spinee.2016.08.001. Disclosure of Interest: None declared